Drama Sebagai Media Dakwah - Iqbal Dawami (LPPM IAIN Sorong, 2018)
Realization of preaching does not only attempt to increase the understanding in behavior and perspective but also to aim the broader target. By the complicated problem of preaching, preaching must be role to aim toward implementation of Islam more overall and share the kinds of life aspect. The preaching media is used for religious teacher to convey the preaching’s messages must be appropriate with condition of society. This matter causes the media of traditional preaching still existing in the center of modern media for present day. One of the traditional preaching media is still used until present day as drama. By drama, preaching can have sent well by the words or face expression. Actualization of preaching’s mission through drama or theater is combination between the art and preaching, so that in developing to aim based on the rules of Islam. Hence, the using of drama as preaching media is really effective because through the locution, movement and action that bundle in a performance of drama so that the preaching’s messages can be sent to the society and it can be as spectacle and the a beneficial guide.